Developing Android-Based Transformational Geometry E-Module Using Adobe Animate CC - Auliya, Nanang Nabhar Fakhri; Zulfikri, Ahmad (Jurnal Pendidikan Matematika, 2023)
This research aims to develop android-based Transformational Geometry e-module teaching material meeting the media eligibility criterion so that it can be implemented as teaching materials for the Transformational Geometry lecture. The research method is Research and Development referring to one of models or learning system design approaches namely the ADDIE model that has been developed by Raiser and Mollenda in the 1990s consisting five stages including analysis, design, development, implementation, and evaluation (feedback). The research subjects involved are two media experts, two teaching materials experts, and thirty 5th semester students of Mathematics Education, IAIN Kudus. The results show that the media experts obtain a total score of 159 with an average score of 79,5 and categorized as “proper”. Based on validation result, the teaching material experts obtain a total score of 166 with an average score of 83 and categorized as “very proper”.  Meanwhile, based on limited and large-scale trials, the total score is 434 with an average score of 86,8 having “very proper” category and 1941 with an average score of 77,64 having “proper” category. Thus, it can be concluded that the android-based Transformational Geometry e-module is suitable to be implemented in learning process in and outside the classroom. Penelitian ini bertujuan untuk mengembangkan bahan ajar e-module Geometri Transformasi berbasis android yang memenuhi kriteria kelayakan media agar dapat diimplementasikan sebagai bahan ajar mata kuliah Geometri Transformasi. Jenis penelitian yang peneliti gunakan adalah metode Research and Development yang mengacu pada salah satau model atau pendekatan desain sistem pembelajaran yaitu model ADDIE yang telah dikembangkan oleh Raiser & Mollenda pada tahun 1990-an, yang terdiri dari 5 (lima) tahap meliputi Analysis (analisis), Design (desain atau perancangan), Development (pengembangan), Implementation (implementasi atau eksekusi), Evaluation (evaluasi atau umpan balik). Subjek uji coba yang terlibat adalah dua orang ahli media, dua orang ahli materi, dan mahasiswa semester 5 program studi Tadris Matematika IAIN Kudus yang berjumlah 30 mahasiswa. Hasil penelitian menunjukkan bahawa ahli media yaitu memperoleh jumlah skor 159 dengan skor rata-rata 79,5, yang termasuk pada kategori “Layak”. Hasil validasi ahli materi memperoleh jumlah skor 166 dengan skor rata-rata 83, yang termasuk pada kategori “Sangat Layak”. Sedangkan pada uji coba terbatas dan uji coba skala besar memperoleh jumlah skor keseluruhan sebesar 434 dengan rerata skor 86,8 dengan kategori “Sangat Layak” dan 1941 dengan rerata skor 77,64 dengan kategori “Layak”. Maka, hal tersebut dapat diambil keputusan bahwa e-module Geometri Transformasi berbasis android layak untuk digunakan dalam proses pembelajaran di dalam kelas maupun di luar kelas.